Nuove strategie per la traduzione del lessico artistico Da Giorgio Vasari a un corpus plurilingue dei beni culturali - Zotti, Valeria; TURCI, MONICA (Lessico multilingue dei Beni Culturali, 2023)
This collection of studies focuses on the translation of the language of art and cultural heritage in a wide variety of text types from the Renaissance to the present, following different theoretical and methodological approaches ranging from corpus linguistics to lexicography, terminology, and translation studies. This book is meant for a wide audience including scholars and students of languages for special purposes, as well as professional translators and experts in the international communication of cultural heritage. These studies have been carried out as part of the Multilingual Cultural Heritage Lexicon research project (Lessico plurilingue dei Beni Culturali). An initiative which first originated at the University of Florence, now involving multiple Italian and international universities, this project is dedicated to compiling textual databases and plurilingual dictionaries through comparable and parallel corpora.